Examination papers from University of Cambridge ESOL examinations: English for speakers of other languagé (Cambridge, 2006)
These past examination papers provide the most authentic exam preparation available. They allow candidates to familiarise themselves with the content and format of the examination and to practise useful examination techniques.
Keywords: Tiếng Anh,English language; Kiểm tra, câu hỏi, v.v.,Examinations, questions, etc